Edible salad bowls (EdiBowls) / Nor Farahani Shamsul Arifin ... [et al.] - Shamsul Arifin, Nor Farahani; Zulkefli, Nur Aina Safira; Burhan, Nur Ameerah Faqihah; Mohd Shahrol, Nurul Syaheera Balqis; Mohamad Husaini, Ziyan Wafiy; Ismadi, Izzat Danish (2025)
EdiBowls is an innovative and eco-conscious healthy food business located in Bukit Jelutong, Shah Alam, a thriving urban center known for its vibrant lifestyle, diverse population, and increasing demand for nutritious, sustainable food options. This restaurant offers a unique dining experience by serving fresh, customizable salads in edible bowls made from natural ingredients, promoting zero waste while delivering high-quality, flavorful meals. Bukit Jelutong was chosen as the ideal location due to its bustling commercial districts, proximity to office spaces, universities, and fitness centers, and a growing community of health-conscious individuals seeking convenient yet wholesome meals. This strategic placement ensures a consistent customer base, including working professionals, fitness enthusiasts, students, and families looking for healthy dining alternatives.